Mapping a WIC Mother's Journey: A Preliminary Analysis. (June 2017) - Panzera, Anthony D.; Bryant, Carol A.; Hawkins, Fran; Goff, Rhonda; Napier, Ashley; Schneider, Tali; Kirby, Russell S.; Coulter, Martha L.; Sappenfield, William M.; Baldwin, Julie; O'Rourke, Kathleen
While the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) provides numerous benefits to many enrolled families across the United States, including access to nutritious foods, some recent drops in maternal participation in Kentucky resulted from failures to retrieve those benefits. We explored perceived benefits of and encountered barriers to food benefit retrieval. Journey mapping included direct observations of client appointments, clinic lobby areas, and a shopping experience and was augmented with focus groups conducted in two urban and two rural areas. Major touchpoints before WIC appointments, during those appointments at clinics, and after appointments when redeeming food benefits were identified. Across touchpoints, mothers identified childcare, transportation issues, long waits, confusion regarding eligibility, problems scheduling appointments, and stigma as barriers to their ability to retrieve food instruments. Despite these barriers mothers value the benefits of WIC, especially access to healthy foods, infant formula, and nutrition education. This work demonstrates a method by which WIC mothers' experiences shed light on client service shortfalls and possible opportunities to improve client services.